Visualizing the Evolution of Islamic Finance Regulation: A Bibliometric Analysis with Graphical Mapping Using Scopus Data - Muhammad Rayhandi Isral; Muthoifin Muthoifin (JESI (Jurnal Ekonomi Syariah Indonesia), 2025)
Introduction: This study examines the global development of Islamic financial regulation by mapping publication trends, thematic structures, and scholarly networks from 1992 to 2025. Despite the rapid growth of the Islamic finance industry, regulatory fragmentation, diverse Shariah interpretations, and inconsistent supervisory practices remain persistent challenges. This study addresses the question: How has Islamic financial regulation evolved in academic literature, and what thematic patterns shape its development? The novelty lies in offering the first bibliometric analysis focusing specifically on Islamic financial regulation. Methodology: Data were retrieved from the Scopus database on July 12, 2025, resulting in 230 journal articles. Bibliometric analysis was performed using Biblioshiny for descriptive metrics, VOSviewer for co-authorship and keyword mapping, and Excel for data organization. The workflow consists of three stages: document identification and screening, data cleaning, and bibliometric and network analysis. Results: The findings reveal consistent publication growth and strong contributions from Malaysia, Indonesia, the United Kingdom, and the United States. Network visualization identifies four dominant clusters: Islamic financial regulation, Shariah governance and compliance, Islamic banking regulation, and Islamic fintech. Highly cited works emphasize regulatory harmonization, supervisory strength, and emerging issues such as digital finance and sustainability.Conclusion: This study concludes that Islamic financial regulation has developed into a dynamic and expanding research field shaped by governance reforms and technological innovation. The results offer valuable insights for academics, regulators, and practitioners by providing a comprehensive overview of research trajectories and future directions.